2010
DOI: 10.1152/ajpregu.00521.2009
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactivity of hydrogen sulfide in normoxic and anoxic turtles (Trachemys scripta)

Abstract: of hydrogen sulfide in normoxic and anoxic turtles (Trachemys scripta). Am J Physiol Regul Integr Comp Physiol 298: R1225-R1239, 2010. First published February 17, 2010 doi:10.1152/ajpregu.00521.2009.-Systemic vascular resistance (Rsys) of freshwater turtles increases substantially during anoxia, but the underlying mechanisms are not fully understood. We investigated whether hydrogen sulfide (H2S), an endogenously produced metabolite believed to be an O 2 sensor/ transducer of vasomotor tone, contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 84 publications
3
11
0
Order By: Relevance
“…Consistent with previous studies on turtles, anoxia caused significant reductions in heart rate and systemic arterial pressure (Hicks and Wang, 1998;Stecyk et al, 2004;Overgaard et al, 2007). Although blood flow was not measured in the present study, earlier studies at a similar temperature have demonstrated a peripheral vasoconstriction mediated by increased sympathetic tone on the systemic vessels (Stecyk et al, 2004), and that H 2 S generation may play some role, particularly at low temperatures (Stecyk et al, 2010). Our study is the first to report on venous pressures in anoxic turtles.…”
Section: Cardiovascular Changes and Role Of Circulating No Metabolitesupporting
confidence: 90%
“…Consistent with previous studies on turtles, anoxia caused significant reductions in heart rate and systemic arterial pressure (Hicks and Wang, 1998;Stecyk et al, 2004;Overgaard et al, 2007). Although blood flow was not measured in the present study, earlier studies at a similar temperature have demonstrated a peripheral vasoconstriction mediated by increased sympathetic tone on the systemic vessels (Stecyk et al, 2004), and that H 2 S generation may play some role, particularly at low temperatures (Stecyk et al, 2010). Our study is the first to report on venous pressures in anoxic turtles.…”
Section: Cardiovascular Changes and Role Of Circulating No Metabolitesupporting
confidence: 90%
“…While undoubtedly initially very useful pharmacological tools in a new but rapidly expanding research field, it is unlikely that these compounds are entirely specific since they target the pyridoxal phosphate (PLP) binding site of CSE and CBS [92] and other PLP-dependent and -independent enzymes (summarized in Table 1). This problem is exaggerated by the disparate concentration ranges commonly used in the laboratory (often used up to 10 mmol/l [93][94][95] …”
Section: Perspectivementioning
confidence: 99%
“…The cardiovascular activity of H 2 S in poikilotherm vertebrates is weakly documented. The available data mainly concern its vasoactive properties that represent a conserved functional trait of this gasotransmitters, being present from fish to reptiles . In the classes so far examined, the gas elicits in vivo and in vitro vasoconstrictory, vasodilatory or multiphasic responses.…”
Section: H2s As a Cardiac Gasotransmittermentioning
confidence: 99%